2018
DOI: 10.1088/1361-651x/aace68
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the predictions of thermo-physical properties of thermoplastic polymers via molecular dynamics

Abstract: We quantify the effect of various sources of uncertainties in the prediction of thermo-physical properties of polymers using molecular dynamics simulations. We quantify how the choice of polymer builder, force field, molecular weight and data analysis affect predicted values of the glass transition temperature (Tg), room temperature density and coefficient of thermal expansion of poly(methyl-methacrylate) (PMMA) and polystyrene (PS). Interestingly, we find that the data analysis introduces significant uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Importantly, this workflow should contain all the pre- and post- processing steps required to turn inputs into outputs. While these steps are often considered unimportant and poorly described in many publications, they can significantly affect results [ 29 ].…”
Section: Sim2ls and The Sim2l Librarymentioning
confidence: 99%
“…Importantly, this workflow should contain all the pre- and post- processing steps required to turn inputs into outputs. While these steps are often considered unimportant and poorly described in many publications, they can significantly affect results [ 29 ].…”
Section: Sim2ls and The Sim2l Librarymentioning
confidence: 99%
“…Uncertainties in classical MD primarily occur for the following reasons: a) the choice of the interatomic potential for a given MD simulation; b) the choice of inputs outlined in Section 1 for DFT calculations of reference properties and the experimental data, which was used to fit the interatomic potential; (c) simplifications to the modeled material when compared to the experimentally characterized material; d) differences in the testing procedures between experiments and simulations; and e) data analysis technique [47]. Most studies show that the choice of the force field is the main factor that affects the predictions of material properties.…”
Section: Uncertainty Quantification Approaches For MD Simulationsmentioning
confidence: 99%
“…The nonbonded long-range electrostatic interactions were described using the particle–particle, particle–mesh method with a precision of 10 –4 kcal/(mol Å) and the nonbonded van der Waals interactions are described using the Buckingham potential with an exponential repulsion and sixth power attraction with cutoff of 12 Å. Our prior work on both thermoplastic , and thermoset , polymers has shown that this force field provides an accurate description of a range of polymers. A timestep of 4 fs was used in all of the simulations using the reversible reference system propagator algorithm (RESPA) multitime step integration with an inner layer timestep of 0.5 fs.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…We calculated the glass transition temperature of bulk systems from the density versus temperature curves using bilinear fit ( T g bilinear ) and hyperbola fit ( T g hyperbola ) to the data, as described in ref , see Figure a. This results in bilinear and hyperbola T g s of 453 and 479 K for PMMA, 442 and 456 K for PS, 246 and 275 K for PP, and 195 and 208 K for PE, respectively.…”
Section: Torsional Relaxation Statistics In Bulk Systemsmentioning
confidence: 99%